Kontestasi dalam Mengelola Amanah: Tata Kelola Lembaga Filantropi Perguruan Tinggi: Contestation in Managing Trust: Governance of University Philanthropic Institutions - Amelia Fauzia, Amelia Fauzia; Sudarnoto Abdul Hakim, Sudarnoto Abdul Hakim; Haryo Mojopahit, Haryo Mojopahit; Gita Safitri, Gita Safitri (Jurnal Bimas Islam, 2023)
In contemporary Indonesia, practices of Islamic philanthropy have been growing rapidly, including in universities, which is home to intellectuals. The practice of Islamic philanthropy in higher education has been developed in various forms, in line with the political democratization and Islamisation after the fall of the New Order. This article analyzes the mapping growth, characteristics, contribution, and challenges of philanthropic practices within universities. This article is based on qualitative research in contemporary Social History. This article discusses the phenomenon of Islamic philanthropy institutions in higher education, following the modernization and Islamization, and positions of universities as civil society. Through in-depth interviews, FGDs, document studies and observation, the authors find that practices of Islamic philanthropy have a significant growth within universities, both in public and private, either secular or Islamic universities, mainly in Java island. The authors find a total number of 51 charitable or philanthropic organizations which have been established within universities, have a diversity in its forms and formation influenced by its own context. These practices are the result of Islamisation and democratization movements that are not only dedicated for strengthening higher educational institutions but also for social welfare and humanitarian purposes. During the Covid-19 pandemics, the practices were becoming stronger. However, the contestation between the state and civil society which has existed in the national level is found also in university level, and becomes one of significant challenges for the pace of development of philanthropy practices in universities. Keywords: Indonesia; Islamic philanthropy; reformation, university, civil society, contestation